Zinc finger protein ZBTB20 expression is increased in hepatocellular carcinoma and associated with poor prognosis - Wang, Qing (BioMed Central, 2011)
BACKGROUND: Our previous studies showed that ZBTB20, a new BTB/POZ-domain gene, could negatively regulate α feto-protein and other liver-specific genes, concerning such as bio-transformation, glucose metabolism and the regulation of the somatotropic hormonal axis. The aim of this study is to determine the potential clinical implications of ZBTB20 in hepatocellular carcinoma (HCC). METHODS: Quantitative real-time RT-PCR and Western blot analyses were used to detect expression levels of ZBTB20 in 50 paired HCC tumorous and nontumorous tissues and in 20 normal liver tissues. Moreover, expression of ZBTB20 was assessed by immunohistochemistry of paired tumor and peritumoral liver tissue from 102 patients who had undergone hepatectomy for histologically proven HCC. And its relationship with clinicopathological parameters and prognosis was investigated. RESULTS: Both messenger RNA and protein expression levels of ZBTB20 were elevated significantly in HCC tissues compared with the paired non-tumor tissues and normal liver tissues. Overexpressed ZBTB20 protein in HCC was significantly associated with vein invasion (P = 0.016). Importantly, the recurrence or metastasis rates of HCCs with higher ZBTB20 expression were markedly greater than those of HCCs with lower expression (P = 0.003, P = 0.00015, respectively). Univariate and multivariate analyses revealed that ZBTB20 overexpression was an independent prognostic factor for HCC. The disease-free survival period and over-all survival period in patients with overexpressed ZBTB20 in HCC was significantly reduced. CONCLUSIONS: The expression of ZBTB20 is increased in HCC and associated with poor prognosis in patients with HCC, implicating ZBTB20 as a candidate prognostic marker in HCC.